2017
DOI: 10.1101/234112
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcription organizes euchromatin similar to an active microemulsion

Abstract: Graphical abstract HighlightsThe copyright holder for this preprint (which was . http://dx.doi.org/10.1101/234112 doi: bioRxiv preprint first posted online Dec. 15, 2017; Page 2 of 46 SummaryThe three-dimensional organization of the genome is essential for development and health. Although the organization of euchromatin (transcriptionally permissive chromatin) dynamically adjusts to changes in transcription, the underlying mechanisms remain elusive. Here, we studied how transcription organizes euchromatin, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 76 publications
2
42
1
Order By: Relevance
“…Тhus, our models indicate that attraction between heterochromatic regions can generate compartmentalization in agreement with Hi-C and global architecture that of inverted nuclei as seen in microscopy. The central role for attractions between heterochromatic regions is in contrast to suggestions from earlier studies concentrated on the role of the lamina 12 and activity-related clustering of euchromatin [13][14][15][16][17] . Importantly, we found that interactions between constitutive heterochromatin ( C , H3K9m3-rich) should be considerably stronger than interactions between facultative heterochromatin ( B , H3K27me3/H4K20me3-rich).…”
contrasting
confidence: 94%
“…Тhus, our models indicate that attraction between heterochromatic regions can generate compartmentalization in agreement with Hi-C and global architecture that of inverted nuclei as seen in microscopy. The central role for attractions between heterochromatic regions is in contrast to suggestions from earlier studies concentrated on the role of the lamina 12 and activity-related clustering of euchromatin [13][14][15][16][17] . Importantly, we found that interactions between constitutive heterochromatin ( C , H3K9m3-rich) should be considerably stronger than interactions between facultative heterochromatin ( B , H3K27me3/H4K20me3-rich).…”
contrasting
confidence: 94%
“…We find that the mir-430 cluster, which is transcribed two orders of magnitude higher than any other region, undergoes a dramatic loss in accessibility when elongation of RNA polymerase II is blocked. The miR-430 cluster is one of the first to be transcribed and initially, all transcribing RNA polymerase II localizes to the two alleles of the miR-430 cluster [19][20][21]56], which might facilitate the formation of RNA-pol II 'trains' capable of evicting nucleosomes, as shown in vitro [33].…”
Section: Locusmentioning
confidence: 98%
“…Thus, it is tempting to speculate that chromatin compartments with different transcriptional activity might display different and tunable degrees of "phase separation" , depending on the type, strength, and dynamics of the physical interactions in each compartment (Fig 2). However, biophysical evidence supporting liquid phase separation of transcriptionally active domains remains sparse (Preprint: Hilbert et al, 2017) and their formation might not necessarily involve such separation.…”
Section: Transcription As a Looping Forcementioning
confidence: 99%